Geomagnetic secular variation consequences on the trajectories of radiation belt trapped particles - Gutierrez Falcón, Alvaro Rafael (2022)
The trajectories of energetic particles trapped by the geomagnetic field, as those composing the Earth’s Van Allen radiation belts, are usually defined by three cyclic motions: gyration, bounce along field lines and drift around the Earth, which are all controlled by this field. The geomagnetic dipole, in turn, has been declining at a rate of ∼5% every hundred years since at least ∼1840. Even with the possibility of a recovery without an extreme event, the global field intensity will very probably continue to decrease in the near future with a consequent weakening of our planet’s magnetic shield capacity. The expected variations in trapped particle trajectories are analyzed in the present work through an analytical approach considering the observed axial dipolar geomagnetic field component and its secular variation. The variations expected on the mirror point altitude and on the boundary of Störmer forbidden zone are assessed along the period 1900-2020. The structures here analyzed could approximate plausible radiation belt changes for a continuously weakening geomagnetic dipole which might have numerous consequences for technologies that operate in space.